Legal Protection In The Processing and Exchange of Personal Data By Financial Technology Companies - Arlini Hapsari Putri Pramudya; Fauzie Yusuf Hasibuan; Zulkarnain Sitompul (Asian Journal of Social and Humanities, 2024)
Technological advances and digitalization in the era of the industrial revolution 4.0 have resulted in changes in the way of working and communication in all aspects of people's lives. One of them is the financial sector with increasingly technology-based services known as financial technology (fintech). In Indonesia, fintech services that are growing rapidly are technology-based lending and borrowing services. This poses a risk of misuse of a person's personal data carried out by the financial service company. The method used in this writing is normative law writing which is carried out as an effort to obtain data related to the problem. The data used is secondary data consisting of primary legal materials, secondary legal materials and tertiary legal materials. Data analysis was carried out using the qualitative juridical analysis method. The results of the writing and discussion get several conclusions, namely that fintech companies must adopt encryption technology and data security to ensure that the personal data transferred is not easily accessed or stolen by unauthorized parties. If a person's personal data as a realm of privacy is misused by unauthorized people, then to create legal protection for users/service customers of fintech companies, the role of law enforcement officials as well as supervisory and regulatory agencies is needed to provide a sense of security for the community, in addition to the need for legal regulations that can ensure community protection.